Endogenous orexin and hyperacute autonomic responses after resuscitation in a preclinical model of cardiac arrest - Guo, Yu; Gharibani, Payam; Agarwal, Prachi; Modi, Hiren; Cho, Sung-Min; Thakor, Nitish V.; Geocadin, Romergryko G. (Frontiers in Neuroscience, 2024)
ObjectivesThe study of autonomic responses to cardiac arrest (CA) resuscitation deserves attention due to the impact of autonomic function on survival and arousal. Orexins are known to modulate autonomic function, but the role of endogenous orexin in hyperacute recovery of autonomic function post-resuscitation is not well understood. We hypothesized that endogenous orexin facilitates hyperacute cardiovascular sympathetic activity post-resuscitation, and this response could be attenuated by suvorexant, a dual orexin receptor antagonist.MethodsA well-established 7-min asphyxial CA rat model was studied. Heart rate (HR) and blood pressure were monitored from baseline to 90-min post-resuscitation. Autonomic function was evaluated by spectral analysis of HR variability, whereby the ratio of low- and high-frequency components (LF/HF ratio) represents the balance between sympathetic/parasympathetic activities. Plasma orexin-A levels and orexin receptors immunoreactivity in the rostral ventrolateral medulla (RVLM), the key central region for regulating sympathetic output, were measured post-resuscitation. Neurological outcome was assessed via neurologic-deficit score at 4-h post-resuscitation.Key resultsA significant increase in HR was found over 25–40 min post-resuscitation (p < 0.01 vs. baseline), which was attenuated by suvorexant significantly (p < 0.05). Increased HR (from 15-to 25-min post-resuscitation) was correlated with better neurological outcomes (rs = 0.827, p = 0.005). There was no evident increase in mean arterial pressure over 25–40 min post-resuscitation, while systolic pressure was reduced greatly by suvorexant (p < 0.05). The LF/HF ratio was higher in animals with favorable outcomes than in animals injected with suvorexant over 30–40 min post-resuscitation (p < 0.05). Plasma orexin-A levels elevated at 15-min and peaked at 30-min post-resuscitation (p < 0.01 vs. baseline). Activated orexin receptors-immunoreactive neurons were found co-stained with tyrosine hydroxylase-immunopositive cells in the RVLM at 2-h post-resuscitation.ConclusionTogether, increased HR and elevated LF/HF ratio indicative of sympathetic arousal during a critical window (25–40 min) post-resuscitation are observed in animals with favorable outcomes. The orexin system appears to facilitate this hyperacute autonomic response post-CA.